STUDI KOMPARATIF PENGAMALAN KARAKTER BANGSA ANTARA SISWA YANG TINGGAL DENGAN ORANG TUA DAN SISWA YANG TINGGAL DI ASRAMA DI SMK NEGERI PERTANIAN TERPADU PEKANBARU - Tampubolon, Veronika; Hambali, Hambali; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by the importance of the nation character practice for learners. And environment as well as good construction can help learners to have a national character, such as environmental practices and the construction of boarding schools and families. The problem of this study “is there a differences between the practice of national character students living with parents and living in a dorm at SMK Pertanian Terpadu Pekanbaru. Character education is now considered essential to be applied so that the inclusion in the curriculum in 2013 but through practice in addition to the natio’s character education curriculum implemented. Parties boarding school and parents also play a role in helping students to have a practice of the natio’s character. The population in this study is the students of class X and XI SMK Pertanian Terpadu Provinsion of Riau. The sample of this study in accordance with the determination of the number of samples developed by Roscoe were 60 respondents from a population of 585 students. Document were collected through observation techniques, questionnaires and studies to library. In analyzing the document using descriptive statistic and quantitative analysis using the formula t_test. From the analysis of the document concluded that : 1) Practice of national character students living with parents and students who live in dormitories SMK Pertanian Terpadu Pekanbaru aqually as very good, 2) Based on statistical analysis of the data showed no significant difference between the practice of national charcter students living with parents and students who live in dormitories SMK Pertanian Terpadu Pekanbaru. Keywords : Practice of national character, students who live with parents, students living in dormitories